Assessment of the plasma start-up in Wendelstein 7-X with neutral beam injection. (5th February 2015) - Gradic, D.; Dinklage, A.; Brakel, R.; McNeely, P.; Osakabe, M.; Rust, N.; Wolf, R.
Abstract: Plasma start-up by neutral beam injection was investigated for stellarators. A zero-dimensional collisional model was extended to evaluate the temporal evolution of the plasma start-up in a confining toroidal magnetic field. Inclusion of different beam energy components indicated a substantial effect due to the energy dependence of beam–gas collisions. Additional collision processes and particle equations were considered to simulate the plasma start-up in helium–hydrogen mixtures. The isotope effect between operation with hydrogen and deuterium beams was also investigated. As a major objective the conditions necessary for a plasma start-up with neutral beams in W7-X have been examined. The assessed beam configuration in W7-X was found not to allow plasma start-up by neutral beam injection alone. The model has been validated for experimental data from W7-AS and Large Helical Device. Quantitative predictions of this study show that the ratio of the beam–plasma interaction length and the plasma volume is an essential quantity for the successful plasma start-up with neutral beams.